PENERAPAN STRATEGI DIGITAL DALAM PELAYANAN PAJAK DAERAH KOTA BANJARMASIN - Puteri, Aulia; Suharto, Imam; Claudia, Meiske (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2025)
This study aims to describe the implementation of digital strategies in regional tax services at the Regional Revenue and Asset Management Agency (BPKPAD) of Banjarmasin City, as well as to identify challenges and public responses to this transformation. Using a qualitative descriptive approach, data was obtained through interviews, observations, and documentation involving BPKPAD employees and taxpayers as informants. The results indicate that digitalization through the "Bijak" application has had a positive impact on administrative efficiency and increased regional tax revenue, especially during the initial implementation phase. However, in practice, various obstacles remain, such as limited digital literacy, uneven internet access, a less user-friendly system design, and concerns regarding data security. Furthermore, a lack of socialization also hinders overall technology adoption. Therefore, the existence of manual services is still necessary to support the transition to an inclusive digital system. Effective interaction between employees and taxpayers is a crucial factor in increasing trust and tax compliance. With a participatory and adaptive approach, the digital strategy is expected to sustainably strengthen regional tax performance.